Functional Outcome of Anterior Surgery for Acute Sub Axial Cervical Spine Injury - Barakoti, Ram Krishna; Bhandari, Pratap Babu; Joshi, Mohan Chandra; Kaucha, Deepak; Chaudhary, Rajesh Kumar; Shrestha, Babu Kaji (Nepal Orthopaedic Association Journal, 2023)
Introduction: Subaxial cervical spine injuries are common following blunt trauma. Unstable cervical spine injuries are frquently managed with anterior decompression and instrumented fusion. This study aims to measure clinical and radiological outcome of anterior surgery for sub-axial cervical spine injuries done in our center. Methodology: This was a retrospective analysis of the cases operated from July 2015-June 2019. Patients aged 18-80 years, presenting with subaxial cervical fractures within 7 days of injury with Sub-axial Injury Classification system (SLIC) score more than 3, managed with anterior surgery were included in the study. Outcome was evaluated at 6 months and at one year with Neck Pain Disability Index and Bridewell Interbody Fusion Grading System. Results: Among 31 patients, ACDF was performed in 14 cases and ACCF in 17 patients. At final follow-up, 43.75% patients had improvement in at least one grade neurology following surgery. Among patients with complete neurological deficit, 25% had minimal disability, 35% moderate, 25% severe and 15% had very severe disability. Similarly, among patients with incomplete neurological involvement, minimal, moderate, severe and very severe disability was seen in 65%, 15%, 20% and none respectively. On average, 90.1% case had grade I fusion, 3.3 % each had grade II, grade III and grade IV fusion. 7 cases had dysphagia which relieved after few days. 1 patient had hoarseness of voice which relieved after few days. Pseudo-arthrosis was seen in 1 case and graft subsidence in 2 cases. Conclusion: Anterior cervical fusion for acute sub-axial cervical spine injuries gives good clinical and radiological outcome with minimal complications.